2014
DOI: 10.4103/0974-7796.127026
|View full text |Cite
|
Sign up to set email alerts
|

A single-center study examining the outcomes of percutaneous epididymal sperm aspiration in the treatment of obstructive azoospermia

Abstract: Introduction:Obstructive azoospermia (OA) is characterized by normal spermatogenesis and the absence of sperm in the ejaculate. Variable success rates have been reported using in-vitro fertilization (IVF) combined with PESA in cases of men with OA.Aims:To determine fertilization and pregnancy outcomes from PESA-derived spermatozoa and to ascertain whether frozen spermatozoa yields similar outcomes compared to fresh specimens.Materials and Methods:The charts of 68 consecutive couples undergoing 68 cycles of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…The spermatozoa obtained were then placed into a sperm buffer and transported to an IVF laboratory. Epididymal spermatozoa were obtained at the same time as oocyte retrieval and used immediately for ICSI [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The spermatozoa obtained were then placed into a sperm buffer and transported to an IVF laboratory. Epididymal spermatozoa were obtained at the same time as oocyte retrieval and used immediately for ICSI [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there is a decrease in sperm production in men with OA, suggested to be a testicular dysfunction resulted of endocrine disruption. The PESA procedure success is usually evaluated by the amount of motile sper-matozoa recovered (Van Perperstraten et al, 2001), and spare spermatozoa can be frozen after ICSI and thawed for a second treatment (Kovac et al, 2014). On the other hand, it is not always possible to recover sperm for cryopreservation, and increased sperm production and motility could contribute to more favorable PESA outcomes, and most likely better ICSI outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Kovac et al retrospectively reported a perfect 100% sperm retrieval rate for 68 patients undergoing PESA between 2002 and 2010. While quantitative sperm parameters and complications were not reported, the pregnancy rate reported with PESA was 48.6% ( 14 ). Hao and colleagues reported a 51% sperm retrieval rate in 96 patients who underwent PESA, although patients with testicular atrophy and elevated FSH were included, possibly diluting the sperm retrieval rate if not all patients had OA.…”
Section: The Step-by-step Guid Ementioning
confidence: 98%
“…After the initial description of epididymal sperm aspiration in 1985 by Temple-Smith et al ( 9 ), the first described percutaneous sperm retrieval in 1994 by Craft and Shrivastav also targeted epididymal sperm, with what is now known as a PESA ( 10 ). Several contemporary series have recently been published of patients who underwent PESA ( 11 - 14 ). Glina and colleagues reported a sperm retrieval rate of 82% in 65/79 patients who underwent PESA, while complications were not reported ( 12 ).…”
Section: The Step-by-step Guid Ementioning
confidence: 99%